2009
DOI: 10.22605/rrh926
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of different subgroups of smear-positive retreatment patients under RNTCP in rural West Bengal, India

Abstract: Outcomes of different subgroups of smear-positive retreatment patients under RNTCP in rural West Bengal, India

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…6 Among retreatment patients the sputum conversion rate at the end of the IP was similar to the observations of Mukherjee and colleagues who reported 72.8%. 7 Favourable treatment outcomes with respect to better cure rates and lesser failure and default rates was seen significantly more in Category I patients compared to Category II patients which was similar to the observations made by Pardeshi and colleagues. 11 This meant that treatment outcome rates in Category II is poor compared to Category I.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…6 Among retreatment patients the sputum conversion rate at the end of the IP was similar to the observations of Mukherjee and colleagues who reported 72.8%. 7 Favourable treatment outcomes with respect to better cure rates and lesser failure and default rates was seen significantly more in Category I patients compared to Category II patients which was similar to the observations made by Pardeshi and colleagues. 11 This meant that treatment outcome rates in Category II is poor compared to Category I.…”
Section: Discussionsupporting
confidence: 86%
“…Relapse as the commonest cause of retreatment was supported by studies by Mehta and colleagues 10 and Mukherjee and colleagues 7 but these other studies found failure as the next most common cause which was different from our study. In another study done in Maharashtra, defaulters constituted the major group among patients put on Category II treatment.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We observed unfavourable outcome commonly among high grade sputum positive patients that is also collaborative with the Mukherjee et al study observations. They also found unfavourable outcome most likely among treatment failure subgroup but we observed it more among treatment after default category patients (46.3%) [ 13 ].…”
Section: Discussionsupporting
confidence: 48%
“…The programme concluded that previously treated patients should undergo drug susceptibility testing and patients with documented resistance (including mono resistance) would receive a regimen based on drug susceptibility results [7]. A retrospective study done in West Bengal among smear positive re-treatment patients reported that unfavorable outcome was more among the treatment failure subgroup and those with high grades of sputum positivity [8]. A systematic review on DOTS for TB relapses in India reported that majority of the relapses presented within six months of treatment completion.…”
Section: Re-treatment Cases and Their Significancementioning
confidence: 99%